A first glance at the work of Dorothy Blumenstock Jones - Rafiza Varão (Revista Mediterránea de Comunicación)
Despite having occupied an important position in the United States Office of War Information (OWI) and having actively participated in a decisive period of Communication Research, Dorothy Blumenstock Jones is a name almost forgotten in the history of the field of communication. All we know about her biography is like some puzzle pieces, although she made significant contributions to the study of movies in the 20th century. This paper seeks to portray not only biographical data about Jones but especially to map her work and its proposals related to the development of film analysis and content analysis - and to place her on the list of pioneers of communication studies.